PROTECTION OF PEACEKEEPING FORCES BASED ON THE CONVENTION ON THE SAFETY - Fitri Rohmadhanita (Lampung Journal of International Law, 2021)
The attacks and threats directed at UN personnel and related personnel resulted in injuries and death. Therefore, to protect these personnel, the GA established a Resolution, namely the Convention on Safety, which aims to protect UN personnel while carrying out its mission. The 1994 Convention on the Safety of the United Nations and Associated Personnel regulates protected personnel and regulates prohibited acts to extradite perpetrators. The Convention urges the host country (Host Country) to determine its jurisdiction in extraditing perpetrators of crimes against personnel UN and related personnel without delay. Given that each country has sovereignty in its territory and is entitled to determine a national legal system that determines national law application based on jurisdiction.